Новые виды и род пилильщиков (Hemenoptera, Tenthredinidae) с острова Сахалин. Сообщение I - Ермоленко, В.М. (Вестник зоологии, 1971)
The description is given of four new for science species o! Tenthredinidae family found in the southern part of Sakhalin and belonging to the subfamily Blennocapinae (Paramasaakia ajnu Ermolenk o sp. п., Rhadinoceraea sachalinensis Ermolenk o sp. n.) and subfamily Allantinae (Empria rubicola Ermolenk o sp. п., Empria loktini Ermolenk o sp. n.) including the new monotypical genus of the first subfamily Paramasaakia Ermolenko , gen. n.